Structural and moadl analysis of rail vehicle car body using finite element method / Darren Ashwin De Silva - Darren Ashwin, De Silva (2018)
Rail vehicles are relatively heavy when compared to other transportation modes. The weight per seat is around three times higher for rail vehicle than for buses. Car bodies of modern rail vehicles are designed as light weight structures with the aim to minimize mass and thus operational energy demand. Weight is a key factor to consider when aiming at reducing the energy consumption as a weight increase of one ton causes an increase for the primary energy demand of 0.0259kWh/tonne.km. Considering the energy demand during the operation phase, composite material is said to be a good design alternative. The structural design of railway vehicle bodies depends on the loads they are subjected to and the characteristics of the material they are manufactured from. During operation the car body is continuously excited due to the dynamic interaction between track, wheels, bogie and car body. The dynamic behavior of railway vehicles relates to the motion or vibration of all the parts of the vehicle and is influenced by the vehicle design. The structural analysis of railway car body is highly intricate due to its dynamic nature. The complexity of contact force developed in the wheel-rail interface strongly influences the dynamic nature of the vehicle. During the research and development of the new transportation solutions, the computational tools can be used to study problems related to the impact of loads asserted on rail vehicle car bodies of existing or future railway vehicles. In this study, the impacts of car body load on the strength of the material, under frame components of the vehicle body, property of the material for the vehicle body are considered.